2010
DOI: 10.1097/tp.0b013e3181e5b811
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Renal Transplant Recipients With Chronic Hepatitis B Infection—Impact of Antiviral Treatments

Abstract: Treatment of HBsAg+ renal transplant recipients with nucleoside/nucleotide analogues confers long-term survival benefit, and that rescue therapy with adefovir or entecavir is effective and well tolerated in patients who had developed resistance to lamivudine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 25 publications
0
65
1
1
Order By: Relevance
“…HbsAg positivity was shown to be an independent risk factor on 10 years patient survival rate (17), and lamivudine treatment was shown to improve survival rate (19,35). In our study, we found that there was no significant difference between the groups in terms of patient and graft survival rates.…”
Section: Discussionmentioning
confidence: 32%
“…HbsAg positivity was shown to be an independent risk factor on 10 years patient survival rate (17), and lamivudine treatment was shown to improve survival rate (19,35). In our study, we found that there was no significant difference between the groups in terms of patient and graft survival rates.…”
Section: Discussionmentioning
confidence: 32%
“…However, when compared with treatment-naïve the virological response could be fluctuating and relatively slow in LAM-R patients [40] . Nevertheless, rescue therapy with ADV resulted in significantly better viral suppression and liver biochemistry compared with continuation of LAM (75% vs 14.3% had persistent normalization of ALT), and the clinical response was sustained for at least 24 mo [31] .…”
Section: Treatmentmentioning
confidence: 99%
“…When compared with untreated patients, those treated with NUCs showed a significant improvement in survival after 20 years of follow up (34% vs 83% respectively, P < 0.006). Even though NUC therapy reduced overall mortality by reducing liver related disease (P < 0.036), 40% of death in chronic HBV infected patients are still related to liver complications and 22.2% of them developed in patients being treated [31] . Forty two RT patients were treated for long term with different NUCs regimens: at the end of follow up 18 patients were receiving monotherapy (9 LAM, 2 ADV, and ETV) and 24 combination therapy (11 LAM + ADV, 2 LAM + TDF, 4 ETV + ADV, 6 ETV + TDF and 1 TDF + emtricitabine, FTC) [60] .…”
Section: Treatment Impact On Long Term Evolutionmentioning
confidence: 99%
See 2 more Smart Citations